Expected Return Dan Risiko Saham LQ-45 Untuk Pengambilan Keputusan Investasi Serta Pembentukan Portofolio Optimal(Capital Asset Pricing Model): Expected Return and Risk of LQ-45 Stocks for Investment Decision Making and Optimal Portfolio Formation (Capital Asset Pricing Model) - Arimarista, Lita (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine the number of groups (clusters) sector, which is for med from the LQ-45 for investment decisions as well as the establishment of an optimal portfolio (Capital Asset Pricing Model). The approach used in this study is quantitative. To test this hypothesis used cluster analysis. The results obtained by Hierarical Cluster Analysis, getting the results that the group ingo eight (8) sectors of 22 shares for med two (2) groups (clusters) . Cluster 1 is a group of sector swith the expected return is not too hight risk is not too high anyway, but Cluster 1 BUMI stock company, INCO and ANTM from the mining sector, and company shares LPKR of the service industry as a high expected return with the higher the risk. Cluster 2 is a group of sectors with the highest expected return with the highest risk anyway. However, Cluster 2 on BBNI company shares of the financial sector has the highest expected return to risk is not too high, when compared with the risk in the shares of other companies which have the expected return is not too high. By using the model of Capital Asset Pricing Model (CAPM) in the calculation and analys is of portfolios .In this study, the portfolio formed from the LQ-45 is AALI, BBNI and GGRM offers a portfolio expected return of 3.00 % and offers portfolio risk by 1.64%.